Peningkatan Pengetahuan tentang Customer Relationship Manajemen (CRM) Tim Pemasaran Rumah Sakit PKU Muhammadiyah Sukoharjo - Noor, Hesty Latifa; Novita Yuliani; Alifah Sari Nugraini; Intan Maharani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
PKU Muhammadiyah Sukoharjo Hospital is a type C hospital that is currently developing offering health services with target service coverage in Sukoharjo Regency. Currently, the marketing team at PKU Muhammadiyah Sukoharjo Hospital is starting to pioneer the development of marketing efforts which are expected to increase patient visits. High competition between hospitals is one of the factors that patient visits at PKU Muhammadiyah Sukoharjo Hospital tend to fluctuate. The marketing team's lack of knowledge regarding marketing strategies and the large number of job desks for each marketing member result in less than optimal marketing efforts. Solutions offered through this Community Service activity (1) Providing education related to Customer Relationship Management (CRM) (2) Providing education related to Customer Relationship Management (CRM) methods (3) Customer Relationship Management (CRM) training that combines processes, people and technology Methods used: (1) Increasing the marketing team's knowledge regarding Customer Relationship Management (CRM) to increase the number of patient visits; (2) Increasing the marketing team's skills in implementing Customer Relationship Management (CRM) methods (3) Increasing and developing strategies to generate users. interface for collecting customer data. The output of this activity is (1) Publication of service results in the Community Service Journal